A Study of the Air Quality in Underground Car Parks with Emphasis on Carbon Monoxide and Airborne Lead - Yaziz, Mohammad Ismail; Yen, A. W. P. (1986)
The concentrations of carbon monoxide and airborne lead in three enclosed underground car parks in Kuala Lumpur were measured simultaneously with traffic flow for a period of three months. The measurements were taken at a height of 1. 5 m from the ground for a duration of8 - 13 hours. A large variation in the airborne lead levels was observed which ranged from 1.75 to 23.9 J1g/m 3 in relation to traffic flow. The mean carbon monoxide concentration ranged from 23.2 to 65.2 ppm. The mean concentration of both pollutants at all the three sites was found to exceed the proposed Malaysian Air Quality Standard of 0.7 J1g/m 3 for lead and 9 ppm (8 hours average) for carbon monoxide. A positive correlation was observed between traffic flow and carbon monoxide as well as lead at the locations studied.